Why can't I learn like everyone else? : youth with learning disabilities - Brinkerhoff, Shirley (Broomall, Pa. : Mason Crest Publishers, 2004)
Examines the most common learning disabilities and explains in a clear and understandable way how these conditions are diagnosed and what help is available to students who have them.
Changes -- Learning to get by -- Anger -- Another world -- Conflicts -- Tensions -- The power of persistence -- Hope.
Includes bibliographical references (p. 121) and index.
Keywords: Learning disabled youth -- Education -- United States -- Juvenile literature; Learning disabilities -- United States -- Juvenile literature; Learning disabilities; Learning disabilities -- Juvenile literature; Slow learing children -- Education -- Juvenile literature